MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS MELALUI MODEL GAME-BASED LEARNING PADA SISWA KELAS IV SDN KARET 01 PAGI JAKARTA - Oky Masayu, Nikita; Usman, Herlina; Sarifah, Iva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocabulary mastery is often an obstacle in learning English for students due to low learning motivation. To overcome this problem, the Game-Based Learning (GBL) approach is applied as an interactive and participatory learning solution. This study aims to improve English vocabulary mastery through the Game-Based Learning model in fourth-grade students of SDN Karet 01 Pagi Jakarta. The subjects of this study were 28 fourth-grade students of SDN Karet 01 Jakarta in the even semester of the 2025/2026 academic year. This study is a Classroom Action Research (CAR) with the Kemmis & McTaggart model, which is implemented in cycles, each consisting of planning, implementation, observation, and reflection stages. Data was collected through written tests, observations, field notes, interviews, and documentation, then analyzed through stages according to Miles and Huberman which include data reduction, data presentation, and drawing conclusions. The results of the study proved a gradual increase in student performance: learning completeness, which was initially only 50% with an average score of 69.57 in cycle I, jumped to 75% with an average score of 79.67 in cycle II, and reached 85% with an average score of 86.57 in cycle III. In addition to the increase in test scores, the results of observations of teacher and student activities after the implementation of the Game-Based Learning model also showed positive developments according to the target. In cycle I, teacher activity was only 64.5% and student activity 58%; in cycle II, teacher activity increased to 79% and student activity 73%; and in cycle III, teacher activity had reached 89.5%, and student activity reached 85.4%. It can be concluded that the Game-Based Learning model can improve students' mastery of English vocabulary. The results of this study can be an alternative action for teachers in implementing the Game-Based Learning model in English learning in elementary schools.